1992
DOI: 10.1128/aem.58.1.243-251.1992
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between marine bacteria and dissolved-phase and beached hydrocarbons after the Exxon Valdez oil spill

Abstract: Turnover times for toluene in Resurrection Bay after the Exxon Valdez grounding were determined to be decades, longer than expected considering that dissolved hydrocarbons were anticipated to drift with the current and stimulate development of additional hydrocarbon-utilizing capacity among the microflora in that downcurrent location. These turnover times were based on the recovery of '4Co2 from added ['4C]toluene that was oxidized. The concentrations of toluene there, 0.1 to 0.2 ,ug/liter, were similar to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The very large value for toluene affinity is consistent with the idea that permeases are not required for hydrocarbon transport but, rather, that such lipid-soluble substrates diffuse directly to a dioxygenase for initial reaction (14). However, some workers suggest that such substrates may be transported ac- a Conversion factors used: 400 mg/liter (wet wt) OD Ϫ1 (30), 3 mg of cells (wet wt) (mg dry wt) Ϫ1 , 1.9 mg of cells (dry wt) mg of protein Ϫ1 .…”
Section: Data Interpretationssupporting
confidence: 77%
See 1 more Smart Citation
“…The very large value for toluene affinity is consistent with the idea that permeases are not required for hydrocarbon transport but, rather, that such lipid-soluble substrates diffuse directly to a dioxygenase for initial reaction (14). However, some workers suggest that such substrates may be transported ac- a Conversion factors used: 400 mg/liter (wet wt) OD Ϫ1 (30), 3 mg of cells (wet wt) (mg dry wt) Ϫ1 , 1.9 mg of cells (dry wt) mg of protein Ϫ1 .…”
Section: Data Interpretationssupporting
confidence: 77%
“…Only the uppermost value of Fig. 3 is sufficient for growth on a single substrate in natural water systems at ambient measured concentrations of substrate which are near 1 g/liter (14,16).…”
Section: Data Interpretationsmentioning
confidence: 96%
“…Robertson and Button (43) observed a continued increase in the blue fluorescence of heterotrophic bacteria at concentrations above 1.0 ,g of DAPI ml-' and used 2.5 ,ug ml-' for best results. However, 0.5 ,ug of DAPI ml-1 has been used in subsequent work by these authors (8). While it is not strictly valid to extrapolate beyond the dye concentrations used in this study, the flatness of the abundance curve beyond 0.5 ,ug ml-' (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Button et al attributed the low K, of a marine Pseudomonas sp. with toluene to its partitioning into the membrane (7). Benson et al (2) showed that components of the alkane hydroxylase of Pseudomonas putida, which converts hydrophobic alkanes to readily water-soluble alkanols, are located in the cytoplasm membrane.…”
Section: Discussionmentioning
confidence: 99%